2015
DOI: 10.1111/cas.12631
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy based on bispecific T‐cell engager with hIgG1 Fc sequence as a new therapeutic strategy in multiple myeloma

Abstract: Bispecific antibodies play an important role in immunotherapy. They have received intense interest from pharmaceutical enterprises. The first antibody drug, OKT3 (muromonab-CD3), showed great performance in clinical treatment. We have successfully developed a single-chain variable fragment (ScFv) combination of anti-CD3 ScFv and anti-CD138 ScFv with the hIgG1 Fc (hIgFc) sequence. The novel bispecific T-cell engager (BiTE) with an additional hIgFc (BiTE-hIgFc, STL001) can target T cells, natural killer cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…Zou et al. found that BiTE‐hIgFc (anti‐CD138‐Scfv‐OKT3‐ScFv‐pFUSE‐hIgFc) binding with T cells and NK cells could achieve potent cytotoxicity against RPMI‐8226 cells and significantly inhibit the growth of tumor in myeloma‐bearing mice . NK cells bearing BiTE‐hIgFc have stronger production of lytic granules and upregulate the expression of activation receptors, which set up a more promising strategy and may provide a new idea for NK cell‐targeted therapy.…”
Section: Novel Nk Cell‐based Immunotherapiesmentioning
confidence: 99%
“…Zou et al. found that BiTE‐hIgFc (anti‐CD138‐Scfv‐OKT3‐ScFv‐pFUSE‐hIgFc) binding with T cells and NK cells could achieve potent cytotoxicity against RPMI‐8226 cells and significantly inhibit the growth of tumor in myeloma‐bearing mice . NK cells bearing BiTE‐hIgFc have stronger production of lytic granules and upregulate the expression of activation receptors, which set up a more promising strategy and may provide a new idea for NK cell‐targeted therapy.…”
Section: Novel Nk Cell‐based Immunotherapiesmentioning
confidence: 99%
“…Other targets addressed with bispecific antibodies include CD38 [98], CD138 [99], CD20 [100], and Wue-1 [101]. …”
Section: T Cells Based Approachesmentioning
confidence: 99%
“…A combination of anti-CD3 scFv and anti-CD138 scFv with the hIgG1 Fc (hIgFc) sequence was developed to form a novel BiTE with an additional hIgFc (BiTE-hIgFc, STL001) [58]. BiTE-hIgFc (STL001) activated T cells effectively and induced cytotoxicity against multiple myeloma cells in vitro and in vivo [58].…”
Section: Bispecific T Cell Engager (Bite)mentioning
confidence: 99%
“…BiTE-hIgFc (STL001) activated T cells effectively and induced cytotoxicity against multiple myeloma cells in vitro and in vivo [58]. It is also the first BiTE to target CD138, CD3, and FcR, which are expressed on multiple myeloma cells, T cells and NK cells, respectively.…”
Section: Bispecific T Cell Engager (Bite)mentioning
confidence: 99%